Morphology, in vivo distribution and antitumor activity of bexarotene nanocrystals in lung cancer. (2nd January 2017) - Wang, Yongjie; Rong, Jinghong; Zhang, Jiaozhen; Liu, Yu; Meng, Xuelian; Guo, Hejian; Liu, Hongsheng; Chen, Lijiang
Abstract: The objective of this study was to develop and evaluate the morphology, biodistribution and antitumor activity of bexarotene nanocrystals delivery system. The morphology was investigated using scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscope and bexarotene nanocrystals exhibited the advantages of making the efficacy more steady and durable compared with control group in lung with less cardiac accumulation as shown by biodistribution studies in vivo . In addition, MTT assay, flow cytometry analysis, observation of morphological changes and apoptotic body demonstrated that bexarotene nanocrystals could significantly enhance the in vitro cytotoxicity and induced G1 cycle arrest and apoptosis against A549 cells. Also, bexarotene nanocrystals had significant antitumor activity in mice bearing A549 cell line. This finding was correlated with both in vitro and in vivo . Thereby, the overall results suggest that the bexarotene nanocrystals represent a potential source of medicine, which made bexarotene nanocrystals a promising candidate for the treatment of lung cancer.